2011
DOI: 10.1162/jocn.2011.21608
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Mechanisms of Cognitive Control for Shifting Attention in Vision and Working Memory

Abstract: Organisms operate within both a perceptual domain of objects and events, and a mnemonic domain of past experiences and future goals. Each domain requires deliberate selection of taskrelevant information, through deployments of external (perceptual) and internal (mnemonic) attention, respectively. Little is known about the control of attention shifts in working memory, or whether voluntary control of attention in these two domains is subserved by a common or by distinct functional networks. We used human functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 66 publications
8
93
1
Order By: Relevance
“…Similarities have been observed with respect to behavioral consequences and neural networks (e.g., Griffin & Nobre, 2003;Nee & Jonides, 2009;Tamber-Rosenau et al, 2011). In light of this evidence, one might question whether making a distinction between external and internal attention is appropriate at all.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Similarities have been observed with respect to behavioral consequences and neural networks (e.g., Griffin & Nobre, 2003;Nee & Jonides, 2009;Tamber-Rosenau et al, 2011). In light of this evidence, one might question whether making a distinction between external and internal attention is appropriate at all.…”
Section: Discussionmentioning
confidence: 55%
“…However, there are also notable differences between the two domains of attentional orienting. For example, neuroimaging studies have found an additional involvement of certain medial and lateral prefrontal areas and stronger activations in parietal regions when the focus of attention is controlled within VWM (Nee & Jonides, 2009;Nobre et al, 2004;Tamber-Rosenau et al, 2011). Moreover, internal attention has also been shown to exhibit distinct behavioral characteristics: Unlike external shifts of attention, internal shifts of attention appear not to be influenced by the initial physical distance of the encoded objects, and beyond a certain threshold time, additional time for internal shifts does not yield additional benefits (Tanoue & Berryhill, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study did find minor group differences in the parietal cortex, but most of the parietal lobe showed no group differences. Whereas DLPFC is implicated in goal-directed behavior, parietal cortex is more involved in directing attention towards salient places, objects, or items in working memory (Curtis and D'Esposito, 2003;Seeley et al, 2007;Tamber-Rosenau et al, 2011). This pattern of findings perhaps suggests that at rest SDI and controls do not differ on lower-level attention aspects of the ECN, but instead, groups differ on higher-level goaldirection and abstract reasoning that is more often associated with DLPFC.…”
Section: The Left Executive Control Networkmentioning
confidence: 97%
“…Moreover, representations in WM are not all in the same state of accessibility, and not all are equally relevant for the current task goals (Oberauer & Hein, 2012;Olivers, Peters, Houtkamp, & Roelfsema, 2011). Investigating how an attentional set can be applied to the representations actively maintained in mind can help shed light onto the control mechanisms of WM and how its contents can be flexibly updated, strengthened, and/or discarded when information about their relevance becomes available (Tamber-Rosenau, Esterman, Chiu, & Yantis, 2011). This special issue honors Steve Yantis and his many contributions to the understanding of the mechanisms of the control of attention.…”
mentioning
confidence: 99%